Review of the matched asymptotic approach of the coupled criterion - Jiménez-Alfaro, Sara; García, Israel García; Doitrand, Aurélien (Comptes Rendus. Mécanique)
Matched Asymptotics is a powerful mathematical technique with broad applicability in various engineering fields. One of its key uses is in Fracture Mechanics, where it provides accurate approximations in the vicinity of the crack tip with low computational complexity. This method can be seamlessly integrated with the Coupled Criterion (CC), which enables the prediction of crack nucleation and propagation in brittle materials. Hence, this paper deeply explains how the MA technique can be applied together with the CC in the context of Fracture Mechanics, providing a detailed literature review of the advances made in the last decade.